2022
DOI: 10.3390/molecules27030879
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antitumor Activities of Newly Synthesized Hesperetin Derivatives

Abstract: Hesperetin is a class of natural products with a wide range of sources and remarkable biological activities. In this study, we described the synthesis of a series of novel hesperetin derivatives and evaluated the in vitro antioxidant and antitumor activity of these compounds. Eleven novel compounds were synthesized in moderate yields. The compounds synthesized in this work exhibited antioxidant activities against DPPH and ABTS free radicals in a dose-dependent manner. Among them, compound 3f had the best antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The compounds with a higher antioxidant activity were found to have lower IC 50 values of DPPH and a higher inhibition percentage against ABTS radicals [40]. It was found that the ABTS assay is more sensitive than the DPPH assay, because the DPPH radical is only involved in hydrogen (H + ) transfer (DPPH to DPPH-H), while the ABTS radical is involved in the electron transfer pathway (ABTS to ABTS + ) [41].…”
Section: Discussionmentioning
confidence: 99%
“…The compounds with a higher antioxidant activity were found to have lower IC 50 values of DPPH and a higher inhibition percentage against ABTS radicals [40]. It was found that the ABTS assay is more sensitive than the DPPH assay, because the DPPH radical is only involved in hydrogen (H + ) transfer (DPPH to DPPH-H), while the ABTS radical is involved in the electron transfer pathway (ABTS to ABTS + ) [41].…”
Section: Discussionmentioning
confidence: 99%
“…Hesperidin suppresses the growth of HeLa cells via blocking endoplasmic reticulum stress pathways and cell cycle arrest-mediated death [ 50 ]. Hesperidin and its derivatives were found to have anticancer effects in HepG2 hepatocarcinoma and HeLa cells [ 51 ]. From this vantage point, it is possible to correlate the biological activity of methanolic extracts from A. gymnolobus with the existence and amount of these chemicals.…”
Section: Discussionmentioning
confidence: 99%
“…Research showed they could inhibit the growth of Plasmodium falciparum (malaria parasite) both in vivo and in vitro [ 45 , 115 ]. In addition, fisetin with quercetin and kaempferol are individually capable of inhibiting the formation of hemozoin [ 45 , 115 , 119 , 182 , 183 ] resulting in the parasite’s death. Moreover, quercetin, fisetin, and kaempferol’s antioxidant and anti-inflammatory roles were proved beneficial for malaria treatments.…”
Section: Main Textmentioning
confidence: 99%